Enhancing Reasoning Capabilities of Small Language Models with Blueprints and Prompt Template Search - Han, Dongge; Xia, Menglin; Madrigal, Daniel; Kessler, Samuel; Mallick, Ankur; Zhang, Xuchao; Hipolito Garcia, Mirian; Xu, Jin; Ruehle, Victor; Rajmohan, Saravan (ICML TTODLer-FM Workshop 2025, 2025)
Small language models (SLMs) offer promising and efficient alternatives to large language models (LLMs). However, SLMs' limited capacity restricts their reasoning capabilities and makes them sensitive to prompt variations. To address these challenges, we propose a novel framework that enhances SLM reasoning capabilities through LLM generated blueprints. The blueprints provide structured, high-level reasoning guides that help SLMs systematically tackle related problems. Furthermore, our framework integrates a prompt template search mechanism to mitigate the SLMs' sensitivity to prompt variations. Our framework demonstrates improved SLM performance across various tasks, including math (GSM8K), coding (MBPP), and logic reasoning (BBH). Our approach improves the reasoning capabilities of SLMs without increasing model size or requiring additional training, offering a lightweight and deployment-friendly solution for on-device or resource-constrained environments.